PROSPEK PEMANFAATAN LIMBAH BATANG PISANG DALAM MENDUKUNG EKONOMI KREATIF MASYARAKAT RAMAH LINGKUNGAN - Hutwan Syarifuddin; Hamzah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Dedication has been carried out in the Farmers Group (Canggam Craftfirra) and Karya Maju Farmers Group on Pematang Rahim Village, Mendahara Ulu District, East Tanjung Jabung Regency. Implementation of service for 8 months from May to November 2018. Objectives for empowering group members in supporting the banana cultivation program and processing banana stem waste as an environmentally friendly paper raw material. The results of dedication activities show that high public interest in utilizing the technology of processing banana stem waste as a raw material for paper to make household handicrafts (home industry) is caused so far Banana stem waste is only wasted and has not been processed into paper pulp. The use of banana stem waste has the advantage of being easily available, easy to do and the price is relatively cheap, so that its use will provide benefits for farmer groups and craftsmen. The prospect of using banana stem waste can be applied to support the creative economy.